Speaker camp workshop - Unger, Russ.; Safari eBooks ([San Francisco, Calif.?] : Peachpit, 2014)
"Conferences abound in most industries, and being a speaker at them can be valuable for anyone's career advancement. This video is about how to market yourself if you want to speak at these events, rather than just sit in the audience. It contains a wealth of tips from two seasoned presenters, from understanding your audience, to finding unique ideas, creating an abstract, crafting a biography, choosing a title, understanding the three parts of a conference proposal, and organizing and structuring content. Speaker Camp Workshop brings alive visual and dynamic examples reinforcing the coverage in the book. Viewers will be able to see what works in real presentations, how to handle practice sessions, manage different types of audiences, the mechanics of presenting material on a stage, and how to control questions and answers--whether friendly or hostile. And it doesn't stop there: it goes on to make suggestions for evaluating and improving your presentation for the next time, incorporating what you've learned from feedback, whether live or through social media."--Resource description page.
Title from resource description page (viewed Apr. 28, 2014).
Keywords: Business presentations; Public speaking; Electronic books